Konuşma Yöntem ve Teknikleri Bakımından Türkçe Ders Kitapları - Doğan, Fatma Nur; Sinan, Ahmet Turan (Bilim Eğitim Kültür Akademi Derneği, 2024)
Bu çalışmanın amacı 6, 7 ve 8. sınıf Türkçe ders kitaplarındaki konuşma etkinliklerini konuşma yöntem ve teknikleri açısından incelemektir. Çalışma nitel yaklaşımda doküman incelemesi yöntemi ile gerçekleştirilmiştir. Çalışma materyali Millî Eğitim Bakanlığı Yayınları’na ve Anka Kuşu Yayınevi’ne ait 6. sınıf Türkçe ders kitapları, Dörtel Yayıncılık’a ait 7. sınıf Türkçe ders kitabı, Millî Eğitim Bakanlığı Yayınları’na ve Ferman Yayıncılık’a ait 8. sınıf Türkçe ders kitaplarıdır. Veriler betimsel analiz yöntemi ile analiz edilmiştir. Çalışma kapsamında bulunan 5 kitaptaki konuşma etkinlikleri konuşma yöntem ve tekniklerine dağılım bakımından incelenmiştir. Araştırma sonucunda bütün sınıf düzeylerinde en fazla güdümlü konuşma yöntem ve tekniğinin kullanıldığı ve dolayısıyla ders kitaplarında konuşma yöntem ve tekniklerinin dengeli bir biçimde dağıtılmadığı saptanmıştır. Bununla birlikte 6. sınıfta Millî Eğitim Bakanlığı Yayınları’na ait kitabın Anka Kuşu’na ait kitaba göre hem konuşma etkinliklerinin sayısı hem de konuşma yöntem ve teknikleri bakımından daha zengin olduğu belirlenmiştir. 8. sınıfta ise Ferman Yayıncılık’a ait kitabın Millî Eğitim Bakanlığı Yayınları’na ait kitaba göre hem konuşma etkinliklerinin sayısı hem de konuşma yöntem ve teknikleri bakımından daha zengin olduğu tespit edilmiştir. Ayrıca konuşma etkinliği sayısı ile konuşma yöntem ve teknik çeşitliliği bakımından 8. sınıf Türkçe ders kitaplarının diğer sınıf düzeylerine göre daha özenli hazırlandığı görülmüştür.

The aim of this study is to examine the speaking activities in 6th, 7th and 8th grade Turkish textbooks in terms of speaking methods and techniques. The study was carried out with the document rewiew method in a qualitative approach. Study material 6th grade Turkish textbooks by the Ministry of National Education Publications and Anka Kuşu Publishing House, 7th grade Turkish textbokk by Dörtel Publishing, 8th grade Turkish textbooks by Ministry of National Education Publications and Ferman Publishing are textbooks. The data were analyzed with the descriptive analysis method. Speaking activities in the 5 books included in the study were examined in terms of distribution of speaking methods and techniques. As a result of the research, it was determined that guided speaking methods and techniques were used the most at all grade levels and therefore speaking methods and techniques were not distributed evenly in the textbooks. However, among the books prepared for the 6th grade, it was determined that the book of the Ministry of National Education Publications was richer in terms of both the number of speaking activities and speaking methods and techniques than the book of Anka Kuşu. Among the books prepared for the 8th grade, it has been determined that the book by Ferman Publishing is richer in terms of both the number of speaking activities and speaking methods and techniques than the book of the Ministry of National Education Publications. In addition, it was observed that the 8th grade Turkish textbooks were prepared more carefully than other grade levels in terms of the number of speaking activities and the variety of speaking methods and techniques
Turkish Textbooks in Terms of Speaking Methods and Techniques
Keywords: Turkish Education; Türkçe Eğitimi